Mining the Final Frontier: Evaluating the Economic Viability of Space Mining; [Minería de la Última Frontera: Evaluando la Viabilidad Económica de la Minería Espacial] - Alam-, M (Universidad Bernardo O Higgins, 2024)
This research examines the prospects for extraterrestrial resource extraction, particularly emphasizing Chile’s distinctive ability to emerge as a leader in this nascent sector. The analysis covers advanced technologies, such as artificial intelligence, robotics, and satellite geospatial analysis, crucial to obtaining materials from extraterrestrial entities, such as asteroids and lunar bodies. Chile’s extensive mining experience, particularly in extreme environments exemplified by the Atacama Desert, positions the country in an advantageous position to adapt these modern technologies to extraterrestrial applications. An assessment of the economic viability of space mining is made, with projections indicating that asteroids may host resources of immense value, potentially amounting to trillions of dollars. However, considerable obstacles are recognized, including significant upfront investments and regulatory impediments. Public-private partnerships are advocated to alleviate financial uncertainties and build on established mining expertise. Furthermore, the importance of technological progress, particularly in autonomous systems and in the use of in-situ resources, is highlighted as a critical element for the success of space mining initiatives. This analysis postulates that, through strategic financial commitments and collaborative efforts, Chile could assume a fundamental role in the future landscape of space mining, thus contributing to economic advancement and resource sustainability. © 2024 Universidad Bernardo O Higgins. All rights reserved.